2008
DOI: 10.1016/j.compscitech.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of deformation mechanisms and failure in thermoplastic multilayer composites

Abstract: To cite this version:Th. Seelig. Computational modeling of deformation mechanisms and failure in thermoplastic multilayer composites. Composites Science and Technology, Elsevier, 2009, 68 (5), pp.1198. <10.1016/j.compscitech.2007.07.017>. C o m p u t a t i o n a l m o d e l i n g o f d e f o r m a t i o n m e c h a n i s m s a n d f a i l u r e i n t h e r m o -p l a s t i c m u l t i l a y e r c o m p o s i t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The traction-opening profile identified during craze thickening is found to decay slightly (as in Elices et al, 2002) while a profile with a constant traction is suggested in Döll (1983), Döll and Könczöl (1990) and Saad-Gouider et al (2006). There are also studies of fracture in PMMA that suggest some softening in the traction-separation profile (Murphy and Ivankovic, 2005) or a combination of softening followed by hardening (Seelig, 2008). Although no general agreement is found in the traction-separation profile, the order of magnitude of the traction during crazing is comparable, the slight differences in the profile still suggest that an approximately constant or decaying traction-opening is realistic.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 93%
“…The traction-opening profile identified during craze thickening is found to decay slightly (as in Elices et al, 2002) while a profile with a constant traction is suggested in Döll (1983), Döll and Könczöl (1990) and Saad-Gouider et al (2006). There are also studies of fracture in PMMA that suggest some softening in the traction-separation profile (Murphy and Ivankovic, 2005) or a combination of softening followed by hardening (Seelig, 2008). Although no general agreement is found in the traction-separation profile, the order of magnitude of the traction during crazing is comparable, the slight differences in the profile still suggest that an approximately constant or decaying traction-opening is realistic.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 93%
“…As the strain rate is low, specimen yields, and due to the strain softening, matrix shear failure and/or interfacial failure will occur [29,34], resulting in interface de-bonding and permanent birefringence after unloading. The bonding lines a little away from the fiber break do not break but orient.…”
Section: Micro-failure Modes Of Sfc Specimensmentioning
confidence: 99%
“…For a low tensile loading rate (2EÀ5 s À1 ), with further loading, the fiber fractures, and almost simultaneously, some lines near the fiber break are disconnected, as the so-called interface de-bonding (Figure 7(b)). As the strain rate is low, specimen yields, and due to the strain softening, matrix shear failure and/or interfacial failure will occur [29,34], resulting in interface de-bonding and permanent birefringence after unloading. The bonding lines a little away from the fiber break do not break but orient.…”
Section: Micro-failure Modes Of Sfc Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Seelig (2007) has performed 2D plane strain finite element studies on PC/SAN, where he used a cohesive zone framework to model crazes, as well as a finite deformation viscoplastic model to account for shear yielding. While Seelig's numerical studies qualitatively indicate higher toughness with increasing PC volume fraction, the three-dimensional synergistic interactions between crazing and shear yielding have not been investigated.5 Baer and co-workers have investigated microlayered laminates in which the outermost layers were constituted of PC.…”
mentioning
confidence: 99%